(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
AI-empowered English lesson design and pedagogy is potentially reconstructing educational practices in middle schools in China. While AI was previously infrequently used in the field of curriculum design, the introduction of tools like Deep Seek have ignited a wave of major innovation. The literature review distills insights from 70 empirical and theoretical studies to identify trends in AI-driven personalized learning, adaptive assessment, and novel instructional design. English teachers are one of education's greatest change agents for decades who are using Deep Seek in tandem with multimedia authoring tools for creating dynamic and engaging lessons. Many private schools, especially in Sichuan province, have also started to use “AI-assisted learning” models, and educational bureaus and large-scale competitions have further encouraged this new development. However, challenges like misalignment with curriculum, ethical problems, and the need for teacher professional development continue. Policy recommendations include adopting a future orientation and promoting training.